A
this is a geometric sequence since there exists a common ratio r between the terms
r = [tex]\frac{21}{7}[/tex] = [tex]\frac{63}{21}[/tex] = [tex]\frac{189}{63}[/tex] = 3
B
to obtain the next term in the sequence multiply the previous term by 3
[tex]a_{n+1}[/tex] = 3 [tex]a_{n}[/tex] ← recursive rule
C
the n th term of a geometric sequence is
[tex]a_{n}[/tex] = [tex]a_{1}[/tex] [tex]r^{n-1}[/tex]
where [tex]a_{1}[/tex] is the first term in the sequence
[tex]a_{n}[/tex] = 7 × [tex]3^{n-1}[/tex] ← explicit rule